Research on English Situational Teaching Assisted by Multimedia and Network - Yadan Wang (Advances in Multimedia)
In order to study situational English teaching, situational English teaching assisted by multimedia and network was analyzed. This kind of teaching method needs to combine video, image, animation, and other processes to support the teaching work, and then it needs to build corresponding teaching scenarios based on actual needs, so that multimedia and network assisted teaching can provide support for students’ English learning with the help of various teaching methods. Multimedia and network assisted English situational teaching has certain advantages and is helpful for later teaching. Therefore, it is necessary to actively use this kind of teaching mode to optimize the English teaching curriculum, lay a good foundation for the subsequent English learning of students, and finally optimize the teaching class of teachers.